Inflation Effects on Finance-Growth Link: A Panel Smooth Threshold Approach - EGGOH, COMLANVI JUDE (My University, 2012)
This paper proposes an original framework to examine whether the strength of the relationship between financial development and economic growth, widely documented in the recent empirical literature, varies with the inflation rate. Using a Panel Smooth Threshold Regression for 71 developed and developing countries over the period 1960--2004, we find a non-linear link between financial development and economic growth: three equilibriums are identified with inflation rate. Then, there is an inflation threshold, for which finance ceases to increase economic growth. Our results suggest that for an inflation rate higher than 20%, economic growth is not, or is negatively, affected by financial development, whereas the impact of finance on growth is positive and significant for an inflation level below 10%.
Keywords: Financial development; economic growth; inﬂation rate; panel smooth regression models